GluN2B mRNA expression and molecular sequence in the brain of pigeons (Columba livia) - Mohammad Rabiul Karim; Ahmed I. Abo-Ahmed; Abu Raihan; Md. Asif Karim Hemel; Md. Alamgir Kobir; Munmun Pervin (Journal of Advanced Veterinary and Animal Research)
Objectives: The current study sought to ascertain the mRNA expression and establish the complementary DNA (cDNA) sequences of pigeon brain's glutamate receptor 2B of N-methyl-D-aspartate (GluN2B) type. Material and Methods: Adult pigeons (Columba livia; n = 8, sharing an equal number of males and females) were used. After proper anesthesia, the brain was exposed, and small pieces of cerebellum, optic tectum, thalamus, and telencephalon were collected quickly; total ribonucleic acid (RNA) was isolated, and cDNA was synthesized for PCR amplification. The ABI Prism 3100 Genetic Analyzer was used to analyze the sequences of the corresponding cDNA fragments. Results: In RT-PCR, the findings unequivocally demonstrated that the pigeon brain's cerebellum, optic tectum, thalamus, and telencephalon all expressed the mRNA for GluN2B. The cDNA sequence of pigeon GluN2B was obtained from PCR-amplified products and included 51 base pairs (bp) of the 5' untranslated region (UTR), a 4,512-bp open reading frame, and 13 bps of the 3' UTR. Pigeon GluN2B's cDNA sequencing displayed 85% identity for human GluN2B and 95% identity for chicken. The amino acid sequences encoded by the pigeon GluN2B gene shared between 85% and 97% similarity with those of humans, rats, and mice. Molecular phylogenetic analysis using the neighbor-joining method showed that pigeon GluN2B is closely related to the GluN2B proteins of these other species. Conclusion: The findings suggest that certain neurons in the pigeon brain produce GluN2B mRNA. They also indicate the presence of various glutamatergic networks and connections within the avian brain. [J Adv Vet Anim Res 2025; 12(2.000): 427-432]